Groundwater System Characteristics of Soe Area, East Nusa Tenggara, Indonesia: The Role of Rock Properties and Structural Geology - Rachman, Muhammad Gazali; Nurwantari, Nanda Ajeng; Wibowo, Eko (Institut Teknologi Adhi Tama Surabaya, 2025)
Groundwater is the primary source of freshwater for communities in Soe Regency, located in the highland of West Timor Island, where surface water resources are limited. This study aims to characterize the groundwater system and assess its sustainability through an integrated approach combining geological mapping, hydrogeological observations, pumping tests, and hydrochemical analyses. Geological mapping identified two dominant lithological units: Quaternary coral limestone, functioning as the main aquifer, and the underlying Noele Formation, where marl layers act as an impermeable base. Hydrogeological surveys revealed four types of spring settings—rock unit contact, fracture-controlled, perched aquifer, and gravel contact springs—demonstrating the role of both karstification and structural controls in groundwater discharge. Groundwater level measurements show that recharge occurs in the northern highlands (elevations up to 1050 m), with flow directed southward and westward towards the Noelmina River. Pumping test results indicate discharge rates ranging from 1 to 11 L/s, with higher productivity in the southern areas. Hydrochemical analysis of 41 water samples shows TDS values of 261–500 mg/L, electrical conductivity of 400–1000 nS/cm (with a localized anomaly of 1200 nS/cm in Hane Village), and pH values of 6.6–8.5, all within safe standards for human consumption.Based on these findings, the Soe groundwater basin is classified into three aquifer productivity zones: moderate, low, and rare. The system is dominated by shallow unconfined aquifers, which remain sufficient in both quality and yield for current needs. However, population growth and urban development pose risks to long-term availability. Therefore, conservation of the northern recharge area is essential, alongside regulation of groundwater abstraction, infrastructure improvements, and exploration of deeper confined aquifers to secure future water resources. This study contributes a comprehensive framework for groundwater system characterization in structurally complex karst environments, providing critical guidance for sustainable water management in semi-arid highland regions.